2008
DOI: 10.1038/sj.ijo.0803801
|View full text |Cite
|
Sign up to set email alerts
|

Past body mass index and risk of mortality among women

Abstract: Background: Epidemiologic studies of body mass index (BMI) in relation to mortality commonly exclude persons with health conditions and/or a history of smoking to prevent bias resulting from illness-related weight loss ('reverse causation'). Analysis of BMI from an earlier time period may minimize reverse causation without requiring exclusion of participants based on disease or smoking history. Methods: We prospectively examined BMI based on technician measurements of weight and height from 10 years prior to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 37 publications
0
21
1
1
Order By: Relevance
“…Almost all studies investigating all-cause mortality have found significantly increased risk at both the lower and the upper ends of the BMI distributions, with constant lower risk of mortality in the middle of the BMI distribution (Manson et al, 1995;Seidell et al, 1996;Calle et al, 1999;Rosengren et al, 1999;Flegal et al, 2005;Breeze et al, 2006;Kivimaki et al, 2008;Moore et al, 2008;Klenk et al, 2009;Prospective Studies Collaboration et al, 2009). Thus, these studies claimed a J-or a U-shaped relationship of BMI with all-cause mortality, but the ideal BMI range where the mortality risk was low has not been consistently defined partly because of the differences in BMI classifications, methods used to estimate mortality risk and partly by different smoking rates within different populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost all studies investigating all-cause mortality have found significantly increased risk at both the lower and the upper ends of the BMI distributions, with constant lower risk of mortality in the middle of the BMI distribution (Manson et al, 1995;Seidell et al, 1996;Calle et al, 1999;Rosengren et al, 1999;Flegal et al, 2005;Breeze et al, 2006;Kivimaki et al, 2008;Moore et al, 2008;Klenk et al, 2009;Prospective Studies Collaboration et al, 2009). Thus, these studies claimed a J-or a U-shaped relationship of BMI with all-cause mortality, but the ideal BMI range where the mortality risk was low has not been consistently defined partly because of the differences in BMI classifications, methods used to estimate mortality risk and partly by different smoking rates within different populations.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well recognized that obesity defined as having a body mass index (BMI) X30 kg/m 2 is associated with many diseases that contribute to premature death, such as cardiovascular disease (CVD), diabetes and certain types of cancers (Hubert et al, 1983;Colditz et al, 1990;Kurth et al, 2002;Calle et al, 2003;Batty et al, 2005;Nyamdorj et al, 2009). However, the association of BMI with mortality of various causes is controversial: a positive (Lee et al, 1993), a J-shaped (Manson et al, 1995;Calle et al, 1999;Moore et al, 2008) or U-shaped (Seidell et al, 1996;Shaper et al, 1997;Rosengren et al, 1999;Baik et al, 2000;Flegal et al, 2005;Breeze et al, 2006;Pischon et al, 2008;Klenk et al, 2009) relation with all-cause mortality; a positive (Lee et al, 1993;Seidell et al, 1996;Flegal et al, 2007;Kivimaki et al, 2008) or a J-shaped (Jonsson et al, 2002) relation with CVD mortality; a positive (Calle et al, 1999(Calle et al, , 2003Hu et al, 2004;Berrington de Gonzalez et al, 2010), a J-shaped (Reeves et al, 2007) relation and no association (Baik et al, 2000;Meyer et al, 2002;Batty et al, 2005;Flegal et al, 2007) with cancer mortality have all been reported.…”
Section: Introductionmentioning
confidence: 99%
“…15,16,[45][46][47][48][49][50] Therefore, it is imperative for studies of lifetime costs to account for differential life expectancy between normal weight and heavier adults.…”
Section: Differential Life Expectancy By Bmimentioning
confidence: 99%
“…This issue of the journal has an original article 1 and two letters 2,3 that address methodologic challenges in the estimation of the impact of body mass index (BMI) on mortality. Recently, large differences in estimates put forward by different investigators [4][5][6][7] have puzzled both the general public and obesity scientists.…”
mentioning
confidence: 99%
“…Moore et al 1 have attempted to estimate the association of BMI with mortality free of confounding, which is a more complex task. The investigators seem to have made the most of an unusual sample and study design to provide information on the BMI-mortality association in women.…”
mentioning
confidence: 99%